2009
DOI: 10.1148/radiol.2523081423
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Tumor Volume Measurement with Combined T2-weighted Imaging and Diffusion-weighted MR: Correlation with Pathologic Tumor Volume

Abstract: Purpose:To retrospectively determine the accuracy of diffusionweighted (DW) magnetic resonance (MR) imaging for identifying cancer in the prostate peripheral zone (PZ) and to assess the accuracy of tumor volume measurements made with T2-weighted imaging and combined T2-weighted and DW MR imaging by using surgical pathologic examination as the reference standard. Materials and Methods:The institutional review board issued a waiver of informed consent for this HIPAA-compliant study. Forty-two patients underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
130
2
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(142 citation statements)
references
References 42 publications
8
130
2
2
Order By: Relevance
“…We found that mean Most of the studies to date that have assessed the utility of DWI in PCa evaluated lesions within the peripheral zone (PZ). Several studies (41)(42)(43)(44) have suggested improvement in tumor detection over T2W, either using DWI alone, or in combination with T2W. Results for comparison between DWI and MRS have been mixed.…”
Section: Discussionmentioning
confidence: 99%
“…We found that mean Most of the studies to date that have assessed the utility of DWI in PCa evaluated lesions within the peripheral zone (PZ). Several studies (41)(42)(43)(44) have suggested improvement in tumor detection over T2W, either using DWI alone, or in combination with T2W. Results for comparison between DWI and MRS have been mixed.…”
Section: Discussionmentioning
confidence: 99%
“…Miao et al [16] showed that the sensitivity and specificity rates for T2WI was 76% and 70% respectively, compared with 86% and 80% for DWI. Combined T2WI and DWI yield slightly better results, with reported sensitivity and specificity rates of 45-89% and 61-97% respectively, compared with 74-85% and 57-95% respectively for DWI alone and 25-87% and 57-92% respectively for T2WI alone [12,15,[17][18][19][20][21][22][23][24][25][26].…”
Section: Potential Uses Of Dwi In Prostate Cancer Detectionmentioning
confidence: 94%
“…Several have suggested improvement in tumour detection over T2WI, either using DWI alone, or in combination with T2WI. Mazaheri et al demonstrated high sensitivity (82%) and specificity rates (95%) using an ADC cut-off of 1.6×10 −3 mm 2 /s [15], while improving tumour volume estimation. Miao et al [16] showed that the sensitivity and specificity rates for T2WI was 76% and 70% respectively, compared with 86% and 80% for DWI.…”
Section: Potential Uses Of Dwi In Prostate Cancer Detectionmentioning
confidence: 99%
“…recurrence location) using follow-up imaging of various lesions [15][16][17][18]. Another imaging approach is to validate the imaging characteristics with biological properties in the surgical specimen [19][20][21][22]. This data-driven approach is attractive because no complete molecular knowledge is needed: the observations drive the identification of treatment-resistant areas in a pragmatic, agnostic way.…”
Section: Strategymentioning
confidence: 99%